Age-related differences in longitudinal associations between alcohol intake and arterial stiffness, pressure wave reflection, and inflammation in male employees. (3rd October 2022) - Takahashi, T; Shina, K; Nakno, H; Fujii, M; Iwasaki, Y; Matsumoto, C; Yamshina, A; Tomiyama, H; Chikamori, T
Abstract: Backgrounds: While arterial stiffness and abnormal pressure wave reflection are independent cardiovascular risk, the difference of their association with alcohol intake have not been fully clarified. Aim: This prospective observational study, which utilized repeated annual measurements performed over a 9-year period, applied mixed model analyses to examine age-related differences in longitudinal associations between alcohol intake and arterial stiffness, pressure wave reflection, and inflammation. Methods: In 4016 middle-aged (43±9 years) healthy Japanese male employees, alcohol intake, brachial-ankle pulse wave velocity (baPWV), radial augmentation index (rAI), and serum C-reactive protein (CRP) levels were measured annually during a 9-year study period. Based on the questionnaire, alcohol intake was classified as non-drinker, mild-moderate drinker (ethanol 1–20 g/day) and heavy drinker (>20 g/day). Results: The estimated marginal mean baPWV (non-drinkers = 1306 cm/s, mild-moderate drinkers = 1311 cm/s, and heavy drinkers = 1337 cm/s, P<0.01) and that of rAI showed significant stepped increases in an alcohol dose-dependent manner in the entire cohort, but an increase in rAI was not observed in subjects aged ≥50 years. The estimated slope of the annual increase in baPWV, but not rAI, was higher for heavy drinkers than for non-drinkers (slope difference, 2.73; P<0.01), especially for subjects aged <50 years. The estimated marginal mean of the serum CRP levels was lower for drinkers than for non-drinkers. Conclusion: In middle-aged male Japanese employees, alcohol intake may attenuate inflammatory activity. While alcohol intake may exacerbate the progression of arterial stiffening in a dose-dependent manner without mediating inflammation, especially in subjects under 50 years of age, it may promote pressure wave reflection abnormalities with aging at earlier ages without further exacerbation at older ages. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Omroncarpis